Jewish Cemetery at Gwarna Street (former Claassenstrasse) in Wrocław: Excavation Report from 2017 and Opportunities for Rescue and Commemoration - Aleksander Limisiewicz; Jerzy Kichler; Agnieszka Jabłońska (Fasciculi Archaeologiae Historicae, 2023)
Excavations in the area of the former Jewish cemetery in Wrocław at Gwarna Street (formerly Claassenstrasse) have been undertaken many times, most recently in 2017. Since the beginning of the 20th century, the cemetery has been subject to urban encroachment which gradually reduced its historic area, forcing two exhumations, followed by devastation in the 1940s under the Nazi regime. The cemetery was formally liquidated in post-war Poland, in the 1950s and 1960s. At that time, the remaining tombstones were removed and part of the area was built over. In order to develop the areas covered by the earlier exhumations, exploration works were carried out to identify the exact area. In 2017, burials from the cemetery were discovered during construction works. Excavations carried out in 2017 revealed seven individual burials, a mass grave with 115 burials in wooden cases, and 5 mass graves from WWII. Within the cases, fragments of pottery from the 18th and 19th centuries were found. The authors discuss the history of the cemetery, details of the 2017 excavation report with analysis, and current efforts to protect and commemorate the area.